«Будиния или Скифия?» Этнокультурная принадлежность населения Среднего Дона в V—IV вв. до н. э. - Гуляев, В.И. (Археологія і давня історія України, 2019)
Статья посвящена рассмотрению давнего спора
об этнокультурной принадлежности населения Среднего Дона в V—IV вв. до н. э. Автор, с помощью
аргументов из области материальной и духовной культуры людей, погребенных в местных курганах,
доказывает их принадлежность к скифам и единому военно-политическому объединению — Скифии. For over half a century (since the end of the 1950s),
the Scythology has been discussing the location of
the Scythian and non-scythian tribes mentioned by
Herodotus on a geographical map. After the Scythian-
Sarmatian conference in 1952 and the report of
B. N. Grakov and A. I. Melyukova, most of archaeologists
supported the idea that only the Black Sea steppe
belonged to the Scythians, and non-scythian peoples
and tribes inhabited the forest-steppe regions of the
Northern Black Sea region. In this regard monuments
on the Middle Don dated V—IV centuries BC began to
be considered Budinia, belonging to the Budinians and
Gelonians. P. D. Lieberov interpreted the Budinians as
Finno-Ugric tribes. Archaeological research of the last
decades (including the widespread use of the methods
of the natural sciences) made it possible to revise this idea and return to the M. I. Rostovtsev and A. I. Terenozhkin
point of view about the existence of a single large Scythia covering in the VII—IV centuries BC all
the Northern Pontic (steppe and forest-steppe) from the Danube to the Don.